2023
DOI: 10.1002/ece3.9648
|View full text |Cite
|
Sign up to set email alerts
|

Variation in adult and pup wolf diets at natal den sites is influenced by forest composition and configuration

Abstract: Although wolves are wide-ranging generalist carnivores throughout their life cycle, during the pup-rearing season wolf activity is focused on natal den sites where pup survival depends upon pack members provisioning food. Because prey availability is influenced by habitat quality within the home range, we investigated the relative importance of prey species for adults and pups and further examined the relationship between habitat characteristics, wolf diet, and litter size on Prince of Wales Island (POW) in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 101 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…We used sterilized tweezers to pluck hair from snares, stored the hair in labeled coin envelopes, and dried at room temperature. During 2015-2018, we also collected wolf scat and shed hair at 13 active den sites within the home ranges of 9 wolf packs in GMU 2 and in the Snow Pass Islands [48]. Although the Snow Pass islands are administratively assigned to adjacent Game Management Unit 3, this area was included in our sample collection efforts because of the proximity to Prince of Wales Island and suspected population connectivity (Figure 1).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used sterilized tweezers to pluck hair from snares, stored the hair in labeled coin envelopes, and dried at room temperature. During 2015-2018, we also collected wolf scat and shed hair at 13 active den sites within the home ranges of 9 wolf packs in GMU 2 and in the Snow Pass Islands [48]. Although the Snow Pass islands are administratively assigned to adjacent Game Management Unit 3, this area was included in our sample collection efforts because of the proximity to Prince of Wales Island and suspected population connectivity (Figure 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…We collected 7891 snagged hair samples from annual monitoring efforts during 2012-2021 and 322 wolf hair samples and 227 wolf scat samples (114 adult scats and 113 pup scats) at active den sites during 2015-2018 [48]. We also collected samples from 14 captured wolves, 580 harvested wolves, and 2 road-killed wolves.…”
Section: Genotypingmentioning
confidence: 99%
“…berries, than previously thought [ 31 ]. In addition, it was found that wolves could use marine resources as well [ 32 , 33 ] and have substantial regional dietary diversity depending on habitat composition season, vegetation patch interspersion [ 33 ].…”
Section: Introductionmentioning
confidence: 99%